Quantum confinement effects in Ge nanocrystals - Miranda, A.; Ramos, A.E.; Nino de Rivera, L.; Cruz-Irisson, M. (Functional Materials, 2005)
The exciton Bohr radius of bulk Ge is larger than that of Si, hence resulting more prominent quantum size effects. In this work, the electron structure of Ge nanocrystals is studied by means a sp³s* tight binding approximation. Comparing the theoretical calculations with experimental data, we conclude that, similar to the case of silicon, the blue-green photoluminescence of Ge nanocrystals probably comes from surface and the size dependent photoluminescence in the near infrared probably involves a deep trap in the gap of the nanocrystals.